Gas Slag Reaction Kinetics in Slag Cleaning of Copper Slags - Chen, Elaine (Xiao Ming) (My University, 2005)
The reduction of iron oxide from slag is involved in many processes, such as, bath smelting, EAF steelmaking and copper slag cleaning processes, and it is known to occur via gaseous intermediates. Four possible rate determining steps are involved during the reduction. Among them, these two interfacial chemical reactions, gas slag and gas carbon could ultimately limit the enhancement of these processes.
In this work, the gas slag reaction kinetics in slag cleaning of copper slags has been studied. The dissociation rate of CO2 on the surface of liquid copper slags is measured using an isotope exchange method, where the mass transfer in the gas phase was eliminated by using a sufficiently high gas flowrate.
It is found that, for slag of the FexO-SiO2-Al2O3-Cu2O system, the apparent rate constant remains fixed with Cu2O content from 1-10 wt pct at higher oxygen potentials. The rate constant becomes approximately 2 times higher after metallic copper is reduced from the slag, this is due to the suspension of small metal drops on the slag surface.
The effect of temperature in the range from 1200-1450°C on the rate constants was also studied. The activation energy was 190 kJ/mole for slag of composition 60FexO30SiO2-1 0Al2O3. In the presence of Cu metal~10%, the activation energy was reduced to 122 kJ/mole.
Keywords: Gas slag, reaction, kinetics, copper slags, gas phase, flowrate